Calcaneal cysts and lipomas: a common pathogenesis? - Malghem, Jacques; Lecouvet, Frédéric; Vande Berg, Bruno (Skeletal radiology, 2017)
Calcaneal cysts and lipomas are relatively rare, benign bone lesions. They are similar in many ways, including in their location and radiological appearance, but their content differs. Cysts contain fluid whereas lipomas contain fat, although some lesions may exhibit a mixed content. The pathogenesis of the two entities is the subject of controversy. The theory that calcaneal cysts may result from lipomatous necrosis has been widely suggested in the literature, but no such progression has ever been shown. The contrary hypothesis has also been considered, i.e., that the content of regressing cysts may be replaced by fatty marrow, leading to a lipoma-like appearance. This second theory is based on indirect arguments, notably that lipomas have a similar location to intraosseous calcaneal ganglion cysts that arise from the subtalar joint and that patients are older in cases of calcaneus lipomas than in cases of calcaneus cysts. We offer an additional argument in favor of this hypothesis. We present an original observation of a calcaneal cyst incidentally discovered in a 15-year-old male whose spontaneous evolution 3 and 7 years later revealed progressive replacement of its fluid content by fat.